2014
DOI: 10.4236/ojst.2014.43024
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Timing of Heavily Destructed Upper First Permanent Molars

Abstract: The first permanent molar as the first permanent tooth in the mouth and with a general insufficient oral hygiene of the children, is commonly subject to significant compromise which may arise due to caries or endodontic complication, or from developmental anomalies such as hypoplasia. Compromised teeth with questionable prognosis may result in short-and long-term clinical dilemmas. The aim of this research is to highlight the factors that require careful consideration when a compromised UFPM is detected and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 6 publications
0
14
0
5
Order By: Relevance
“…Eight of the included studies were cross-sectional [1219], two were case-control [7, 20], and one was prospective and observational [21]. One study [12] was excluded because the data for malocclusion as an outcome of FPM extraction were invalid; in addition, the criteria used to classify normal and abnormal malocclusion were not uniform or acceptable.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight of the included studies were cross-sectional [1219], two were case-control [7, 20], and one was prospective and observational [21]. One study [12] was excluded because the data for malocclusion as an outcome of FPM extraction were invalid; in addition, the criteria used to classify normal and abnormal malocclusion were not uniform or acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…Rahhal [12, 21] studied the timing of extraction of severely decayed upper FPMs. In his sample of children (mean age 10.5 years) who underwent extraction of an upper FPM, Rahhal found that 84.6% of upper SPMs had complete space closure without any orthodontic intervention and only 15.4% of upper SPMs erupted 1 mm distal to the second premolar.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations